Toll-like receptor cascade and gene polymorphism in host–pathogen interaction in Lyme disease - Rahman S; Shering M; Ogden NH; Lindsay R; Badawi A (Dove Medical Press, 2016)
Shusmita Rahman,1 Maria Shering,2 Nicholas H Ogden,3 Robbin Lindsay,4 Alaa Badawi1 1National Microbiology Laboratory, Public Health Agency of Canada, Toronto, 2Faculty of Arts and Science, University of Toronto, Toronto, ON, 3National Microbiology Laboratory, Public Health Agency of Canada, Saint-Hyacinthe, QC, 4National Microbiology Laboratory, Public Health Agency of Canada, Winnipeg, MB, Canada Abstract: Lyme disease (LD) risk occurs in North America and Europe where the tick vectors of the causal agent Borrelia burgdorferi sensu lato are found. It is associated with local and systemic manifestations, and has persistent posttreatment health complications in some individuals. The innate immune system likely plays a critical role in both host defense against B. burgdorferi and disease severity. Recognition of B. burgdorferi, activation of the innate immune system, production of proinflammatory cytokines, and modulation of the host adaptive responses are all initiated by Toll-like receptors (TLRs). A number of Borrelia outer-surface proteins (eg, OspA and OspB) are recognized by TLRs. Specifically, TLR1 and TLR2 were identified as the receptors most relevant to LD. Several functional single-nucleotide polymorphisms have been identified in TLR genes, and are associated with varying cytokines types and synthesis levels, altered pathogen recognition, and disruption of the downstream signaling cascade. These single-nucleotide polymorphism-related functional alterations are postulated to be linked to disease development and posttreatment persistent illness. Elucidating the role of TLRs in LD may facilitate a better understanding of disease pathogenesis and can provide an insight into novel therapeutic targets during active disease or postinfection and posttreatment stages. Keywords: Lyme disease, Toll-like receptors, Borrelia lipoproteins, genetic polymorphisms, host–pathogen interaction